Bi-Luminal Mitral Valve: Incidence, Clinical Features, Associated Anomaly and Echocardiographic Evaluation - Sinha, Santosh Kumar (J Clin Med Res, 2016)
OBJECTIVE: The aim of the study was to know the incidence, clinical features, associated anomaly and echocardiographic evaluation of bi-luminal mitral valve (also known as double orifice mitral valve or DOMV) in patients with suspected mitral valve disease, continous murmur or left-to-right shunt. METHODS: Twenty-eight patients with DOMV were diagnosed by transthoracic echocardiography (TTE) in a retrospective review of 52,256 echocardiographic studies in 45,898 patients performed between 2000 and 2015. RESULTS: The mean age was 20.1 years (15 - 34 years) with female preponderance (M/F: 1:1.8). Dyspnea and diastolic murmur were the most common symptoms found in 19 (67.8%) and 19 (67.8%) of patients, respectively. Normal sinus rhythm was the most common electrocardiographic finding. Twenty-five (89%) patients had complete bridge, while three (11%) had incomplete bridge type of DOMV. Twenty-one (75%) had severe mitral stenosis (MS) including severe tricuspid regurgitation (n = 13, 61%), ventricular septal defect (VSD, n = 3, 14%), complete endocardial cushion defect (ECD, n = 3, 14%), and mild to moderate mitral regurgitation (MR) (n = 2, 11%), moderate MS and moderate MR were found in four (16%) patients among complete bridge type of DOMV, while all patients with incomplete bridge type had severe MS and patent ductus arteriosus (PDA) as associated lesions. Overall, 24 (85%) had severe and four (15%) had moderate MS. CONCLUSIONS: DOMV as a cause of symptomatic mitral valve disease was seen in young and middle-aged patients with estimated incidence of 0.06%. Dyspnea and diastolic murmur were the most common symptoms. Mostly, it was an isolated anomaly but in majority, associated with VSD, complete ECD and PDA. TTE examination is a reliable and sufficient means of diagnosing DOMV and determining its type.